CODE SWITCHING AMONG INDONESIAN YOUTUBERS - Suastika, I Wayan Endra Setiawan; Putra, I Gede Adiyana; Prawira, Bagus Yuda (Universitas Pendidikan Ganesha, 2020)
This study aimed to analyse the types and function of code-switching by employing the theory of Poplack [12] as well as Appel and Muysken [13]. The data were gathered through the qualitative method by transcribing and analysing the videos to find out the types and function of code-switching. The data were the utterances uttered by three YouTubers namely Boy William, Sheryl Sheinafia, and Agung Hapsah in three separated videos. This study was conducted in three stages such as transcribing the videos into written form, analysing it, then categorizing it into the types and functions of code-switching. The result of the study shows that out of 86 utterances of Boy William, 39 utterances are Intra-Sentential Code-Switching, 3 utterances are Inter-Sentential Code-Switching, 27 utterances are extra-sentential code-Switching, and also 3 utterances with expressive function, 10 utterances with phatic function, 32 utterances with metalinguistic and 2 utterances with poetic function. For Sheryl Sheinafia, the result shows that out of 68 total utterances, 12 utterances are intra-sentential code-switching, 9 utterances are inter-sentential code-switching, and 14 utterances are extra-sentential code-switching, also 3 utterances with expressive function, 3 utterances with metalinguistic function, and 3 utterances with phatic function. The study also shows that out of 30 utterances uttered by Agung Hapsah, 4 utterances are Inter-sentential, 10 utterances are Intra-sentential and 5 utterances are extra-sentential code-switching, also 3 utterances with expressive function, 3 utterances with metalinguistic function and 1 utterance with poetic function.